A reading of the position of women in the Qur'an - Mohammed, Shirin Saleh (Sulaimani Journal for Humanities, 2026)
Women are intelligent people with their own attitudes and thoughts, according to their physical and spiritual abilities, which God has given them and based on the circumstances and time of the society in which they live. Therefore, in our time, issues related to women have become one of the main topics for research and discussion. In this regard, the aim of this research is to know the position of women in the Qur'an as the first source of Islam Islam has been the worst situation for women in general and in the Arabian Peninsula in particular, to the extent that the birth of girls was a shame and sometimes killed He does not distinguish between men and women in any of the duties, commandments and punishments, but sometimes facilitates them in worship according to their circumstances. In addition, he commands that women be treated well and rejects any violence and insult against them.